New Structural Economics : A Framework for Rethinking Development - Lin, Justin Yifu (World Bank, Washington, DC, 2014)
As strategies for achieving sustainable growth in developing countries are re-examined in light of the financial crisis, it is critical to take into account structural change and its corollary, industrial upgrading. Economic literature has devoted a great deal of attention to the analysis of technological innovation, but not enough to these equally important issues. The new structural economics outlined in this paper suggests a framework to complement previous approaches in the search for sustainable growth strategies. It takes the following into consideration: First, an economy's structure of factor endowments evolves from one stage of development to another. Therefore, the optimal industrial structure of a given economy will be different at different stages of development. Each industrial structure requires corresponding infrastructure (both "hard" and "soft") to facilitate its operations and transactions. Second, each stage of economic development is a point along the continuum from a low-income agrarian economy to a high-income industrialized economy, not a dichotomy of two economic development stages ("poor" versus "rich" or "developing" versus "industrialized"). Industrial upgrading and infrastructure improvement targets in developing countries should not necessarily draw from those that exist in high-income countries. Third, at each given stage of development, the market is the basic mechanism for effective resource allocation. However, economic development as a dynamic process requires industrial upgrading and corresponding improvements in "hard" and "soft" infrastructure at each stage. Such upgrading entails large externalities to firms' transaction costs and returns to capital investment. Thus, in addition to an effective market mechanism, the government should play an active role in facilitating industrial upgrading and infrastructure improvements.